The Minimum Wage and Union Membership among Minimum Wage Workers: Why Do Unions Advocate for Minimum Wage Increases? - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2022)
Over the past decade, organized labor has played a significant role in advocating for minimum wage increases. In this paper, we investigate the effects of minimum wage increases on union membership among individuals in minimum wage intensive industries. Consistent with a "freeriding" hypothesis, we find that minimum wage increases predict declines in union membership among low-skilled's most direct beneficiaries. We find no evidence of a change in union membership among high-skilled workers in these industries.
Keywords: D71; D78; P16; 330; political economy; social choice; minimum wage; unionization